IMF Survey, Volume 35, Issue 02. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
De Rato in Brazil; Article IV summaries: Pakistan, Ukraine, CEMAC; Dawson on IMF's transparency revolution; Capital flight, institutions, and instability; Eastern Caribbean; Germany's regulation; Kazakhstan's non-oil sector; Trade, aid, and growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet